Keadilan Gender dalam Pendidikan Islam di Pondok Pesantren - Sumaryati, Sumaryati (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2018)
This paper describes gender justice in Islamic education in Islamic boarding schools that has not been done optimally. This is due to cultural constraints which have resulted in a less gender responsive policy, namely the patriarchal system. In the patriarchal system men control women's work. The implication is that santri occupy the main authority in the pesantren environment. In analyzing the nature and culture theory, women and their functions are identified with